A facile method to synthesize BaZr0.1Ce0.7Y0.1Yb0.1O3-δ (BZCYYb) nanopowders for the application on highly conductive proton-conducting electrolytes. (5th December 2022) - Zhong, Zhaoyu; Li, Zhaoqiang; Li, Jiao; Guo, Xue; Hu, Qiangqiang; Feng, Yurun; Sun, Haibin
Abstract: BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3-δ (BZCYYb), one kind of promising electrolyte materials for proton-conducting solid oxide fuel cells (H + -SOFCs), generally suffers from the poor sinterability, leading to poor electrochemical performances lower than expected. Herein, a facile method, modified room temperature solid-state reaction (M-RTSSR) was proposed for synthesizing highly active BZCYYb nanopowders. Pure perovskite BZCYYb powders can be obtained at a low calcination temperature of 950 °C and a short dwelling time of 3 h. The highly active character allows the sintering temperature of BZCYYb electrolytes decrease from 1550 °C to 1450 °C, thus effectively suppressing the Ba evaporation and promoting the grain growth. The electrical conductivity measured at 700 °C in wet air is 2.6 × 10 −2 S cm −1, which mainly benefits from the improvement of grain boundary conductivity. According to the analysis based on space charge layers, the enhanced electrical performance can be ascribed to their lower space charge potential (Δ φ (0) ) and higher impurity blocking item ( ω/d g ). Finally, the anode-supported single cell with such BZCYYb electrolytes reaches a peak power density of 0.54 W cm −2 at 700 °C while taking humid H2 (∼3 vol% H2 O) as fuels and ambient air as oxidants. Highlights: A facile method is firstly proposed to synthesize highly active BZCYYb nanopowders. The calcination temperature of pure BZCYYb nanopowders is decreased to 950 °C. The sintering temperature of densified BZYCCb electrolytes is decreased by 100 °C. The electrical conductivity of 2.6 × 10 −2 S cm −1 at 700 °C in wet air is achieved. The mechanism of enhanced electrical performances is clarified.